2012
DOI: 10.1017/s1368980012000602
|View full text |Cite
|
Sign up to set email alerts
|

Age, marital status and changes in dietary habits in later life: a 21-year follow-up among Finnish women

Abstract: Objective: To examine 21-year longitudinal changes in dietary habits and their associations with age and marital status among women aged 50-60 years at baseline. Design: Prospective, longitudinal study of a cohort in the FINMONICA populationbased risk factor survey with clinical assessments in 1982, 1992 and 2003. Dietary habits were assessed via self-reported consumption of foods typically contributing to SFA, cholesterol and sugar intakes in the Finnish diet. A dietary risk score based upon five items was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
1
9
0
2
Order By: Relevance
“…Worldwide, few studies have specifically examined longitudinal intra-individual changes in diet quality in adult and that have compared these changes with the national dietary recommendations [ 8 , 11 17 , 19 ]. In general terms, these cohorts have also shown improvements in food patterns, as we found in our investigation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Worldwide, few studies have specifically examined longitudinal intra-individual changes in diet quality in adult and that have compared these changes with the national dietary recommendations [ 8 , 11 17 , 19 ]. In general terms, these cohorts have also shown improvements in food patterns, as we found in our investigation.…”
Section: Resultsmentioning
confidence: 99%
“…There was a reduction in the consumption of butter, high-fat milk products, eggs and sugar and an increase in the consumption of vegetable oils in cooking, low-fat and fat-free milk products. Overall, change was generally in a positive direction [ 8 ]. Finally, several investigations about changes in diet and profile of energy and nutrient intakes in British birth cohort over 8 or 17 years, suggested that most of the trends observed are in line with the accepted dietary guidelines and with our results, such as the increased consumption of fruit and vegetable and a shift away from whole milk and red meat [ 11 , 13 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous evidence suggests that those living solitary are more likely to have poorer dietary patterns [ 60 62 ]. In a longitudinal study improvements in dietary behaviours over 21 years in women were demonstrated whether they remained married or became single [ 63 ]. Another longitudinal study demonstrated remarriage or cohabitation had a positive effect on diet while marital break-up had adverse effects on diet and other health behaviours [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 ] In another study, the score of unhealthy diet decreased in Finnish women aged 50-60 years over a 20-year period. [ 27 ]…”
Section: Discussionmentioning
confidence: 99%